Does oxidative stress contribute to adverse outcomes in HIV-associated TB?. (8th January 2018) - Yew, Wing-Wai; Chan, Denise P; Singhal, Amit; Zhang, Ying; Lee, Shui-Shan
Abstract: In HIV infection, oxidative stress is a pronounced phenomenon, with likely links to HIV-related pathologies and the progression of HIV infection per se . TB is an AIDS-defining condition. HIV-associated oxidative stress, like that associated with diabetes mellitus, might adversely impact the outcomes of TB, probably through increased propensity for generation of metabolically dormant mycobacterial persisters, alongside other mechanisms. This hypothesis might help in guiding the exploration of relevant research directions to improve the care of patients.